Analysis of adverse reactions and cost-driving factors during the induction phase of pediatric acute lymphoblastic leukemia - Xu, Zhonghao; Jia, Chenhong; Ding, Xiangyu; Chen, Xiaohui (Frontiers in Pediatrics, 2025)
IntroductionAcute lymphoblastic leukemia (ALL) is the most common pediatric malignancy and incurs high medical costs due to the complexity and duration of treatment. This study aimed to analyze the incidence of adverse reactions during the induction phase of ALL treatment and identify key factors influencing hospitalization costs.MethodsA retrospective analysis was conducted on 292 newly diagnosed cases of ALL in children who received induction therapy at Hebei Children's Hospital (2020–2024) under the CCLG-ALL-2018 protocol. Demographic, clinical, laboratory, and hospitalization cost data were collected. Adverse reactions were graded using the Common Terminology Criteria for Adverse Events version 5.0. Hospitalization costs were analyzed using the structural variation method and grey relational analysis. Multivariate linear regression was performed to identify cost-related factors.ResultsThe median patient age was 4.9 years (male:female = 6:4). Most cases were B-cell ALL (88.36%), and 69.52% were classified as intermediate risk. Adverse reaction rates were relatively low, including allergic reactions (2.74%), pancreatic toxicity (3.77%), and hepatotoxicity (13.36%). Infections were common, with sepsis occurring in 49.32% and pneumonia in 32.19% of cases. The mean hospitalization costs during the induction phase decreased from 77,690 RMB in 2020 to 56,263 RMB in 2024. Diagnostic fees (37.55%) and medication (30.52%) represented the largest cost components. Hospitalization days, intravenous antifungal medication, tumor lysis syndrome, blood product usage, severe pneumonia infection, surgery performed and discharge yearwere determined to be independent predictors of increased costs.ConclusionsAdverse reactions and complications markedly burden induction treatment. Optimizing protocols, improving monitoring, and implementing cost-control measures can enhance outcomes and reduce costs. Larger sample sizes and socioeconomic variables should be included in future research.